2014
DOI: 10.3136/fstr.20.295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Chrysin Supplementation on Blood Pressure and Oxidative Status of Rats Fed a High-Fat High-Sucrose Diet

Abstract: Effects of dietary chrysin supplementation on blood pressure and oxidative status of rats were studied in comparison with quercetin. Rats were fed a control diet or a high-fat high-sucrose (HFS) diet with or without 0.25% flavonoids (chrysin or quercetin) for 4 weeks. In rats fed the HFS diet without flavonoids, there was a significant elevation of blood pressure, increase in aortic NADPH oxidase but not xanthine oxidase, an increase in plasma lipid peroxides, and a decrease in liver glutathione, compared to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is present in propolis, honey, passion fruit, mushrooms and other plant sources; it has been used to treat numerous types of degenerative disorder and exhibits anti-inflammatory activity ( 34 - 36 ). In addition, it has been used in the treatment of numerous types of metabolic malfunction, such as metabolic syndrome ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is present in propolis, honey, passion fruit, mushrooms and other plant sources; it has been used to treat numerous types of degenerative disorder and exhibits anti-inflammatory activity ( 34 - 36 ). In addition, it has been used in the treatment of numerous types of metabolic malfunction, such as metabolic syndrome ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chrysin was marked in herbs of Scutellaria galericulata L. [4], and Passilora caerulea L. [86,87]. Chrysin showed various pharmacological effects, such as anti-inflammatory [88], antioxidant [89], and antihypertensive activity [86,90,91,95], neuroprotective [86], anticancer properties [86], possessed protective effects against toxic agents [92], and many others [86].…”
Section: Natural Source and Pharmacological Profilementioning
confidence: 99%
“…administered to rats with hypertension caused by N-nitro-Larginine methyl ester showed antihypertensive effect throughout the following mechanism of action such as: reduction in functions of left ventricular, oxidative stress in cardiac tissue and level of angiotensin II in plasma, and increasing of hexooxygenase in cardiac tissue, concentration of cGMP and a prevention of plasma nitric oxide loss. Other study was carried out to estimation of effects of chrysin supplementation on blood pressure of rats fed a high-fat and highsucrose diet in comparison with quercetin [95]. Results showed that chrysin suppressed the elevation of blood pressure in normotensive rats and exerted an antihypertensive effect similar to quercetin.…”
Section: In Vivo Studies Related To the Various Models Of Hypertensionmentioning
confidence: 99%
“…Chrysin is a natural flavonoid present in honey, propolis and diverse plant extracts (German-Ponciano et al, 2018), and is one of the most studied polyphenolic nutraceuticals (Chadha et al, 2017). Chrysin is used as a nutraceutical as a "testosterone boosting agent" (a claim that is probably very exaggerated; Gambelunghe et al, 2003), but there is some preclinical evidence that this molecule ameliorates indices of hepatic and renal functioning in diabetic animals (Ramanathan & Thekkumalai, 2014;Yamamoto, 2014). There is also preclinical evidence that this flavonoid exerts anxiolytic-like effects (Wolfman et al, 1994;Salgueiro et al, 1997;Zanoli et al, 2000;Rodríguez-Landa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%